Polymorphism of regulatory region of GHRL gene (‐2531C>T) as a promising predictive factor for radiotherapy‐induced oral mucositis in patients with head neck cancer. Issue 8 (22nd March 2018) - Brzozowska, Anna; Homa‐Mlak, Iwona; Mlak, Radosław; Gołębiowski, Paweł; Mazurek, Marcin; Ciesielka, Marzanna; Małecka‐Massalska, Teresa
Abstract: Background: The purpose of this study was to investigate the relationship between single nucleotide polymorphisms (SNP; rs1629816) in the regulatory region (c.‐2531C>T) of the ghrelin ( GHRL ) gene and the occurrence and severity of oral mucositis caused by radiotherapy (RT) in patients with head and neck cancer. Methods: Oral mucositis in 65 patients with head and neck cancer who underwent irradiation were assessed according to Radiation Therapy Oncology Group (RTOG)/European Organisation for Research and Treatment of Cancer (EORTC) scale. The DNA from patients with head and neck cancer was isolated from whole blood. The genotypes were determined using the minisequencing method (SNaPshot PCR). Results: The frequency of occurrence of the GHRL gene (c.‐2531C>T, rs1629816) genotypes were as follows: AA = 21.5%; GA = 40%; and GG = 38.5%. In case of AA genotype, there was a 7‐fold decrease of the risk of occurrence of oral mucositis (of grades 2 and 3) in the sixth week of RT (AA vs GA or GG, respectively: 17.9% vs 82.1% patients; odds ratio [OR] 0.14; 95% confidence interval [CI] 0.02‐0.98; P = .0481). No statistically significant differences were observed between the volume of oral cavity contours (V30, V40, and V50) depending on the GHRL genotype in patients with head and neck cancer. Conclusion: The study results have demonstrated an association between the AA genotype of the GHRL gene and the risk of more severe oral mucositis attributed to RT in patients with head and neck cancer.